INFLUENCE OF PRICE AWARENESS, BRAND IMAGE, AND SELF-CONCEPT ON PURCHASING BEHAVIOUR TOWARDS THE FASHION APPAREL INDUSTRY AMONG GENERATION Y CONSUMERS IN MALAYSIA - Lee , Bruce Jack; Kiong , Tee Poh; Dada , Morakinyo (Electronic Journal of Business and Management, 2022)
This research investigates three independent variables—price awareness, brand image, and self-concept—and their influence on the purchasing behavior of Generation Y consumers in Malaysia’s fashion apparel industry. The study also examines if there is a significant difference in behavior based on gender. The ABC Model of Attitude (Affect, Behavior, and Cognition) is used as the underpinning theory, explaining how consumers change their thinking, feeling, or acting toward a product. This is a quantitative study where data collected via questionnaires was analyzed using SPSS version 25.0. The findings aim to help marketers and organizations better understand consumer psychology in the current Malaysian market.